Postoperative pulmonary complications following major head and neck cancer surgery. Issue 3 (March 2021) - Shaw, L.M.; Iseli, T.A.; Wiesenfeld, D.; Ramakrishnan, A.; Granger, C.L.
Abstract: The primary aim of this observational study was to describe the incidence of postoperative pulmonary complications (PPCs) in 60 consecutive, surgically treated head and neck cancer patients requiring free flap reconstruction and tracheostomy, using both a prospective and a retrospective outcome measure. Secondary aims were to identify risk factors for PPC development, explore the effects of PPC on outcomes, and describe the provision of postoperative physiotherapy in this population. Postoperative pulmonary complications occurred in nine (15%) patients based on the Melbourne Group Scale and 27 (45%) patients based on Health Information Service coding data. The occurrence of a PPC was not statistically correlated with age, smoking history, comorbidities, operative time, or type of resection or free flap. Patients who developed a PPC, compared to those who did not, had a higher preoperative body mass index ( P = 0.022) and were more likely to be sat out of bed earlier post-surgery ( P = 0.038). Overall, patients required a median of 9.0 (interquartile range 7.0–11.0) physiotherapy sessions. Patients developing a PPC required significantly more physiotherapy sessions ( P = 0.007) and additional days of supplemental oxygen ( P = 0.022) as compared to those without a PPC, despite a similar hospital length of stay. In future, targeted physiotherapy interventions may reduce PPCs in this population.